Effect of microchannel junction angle on two-phase liquid-gas Taylor flow. (20th July 2019) - Lim, An Eng; Lim, Chun Yee; Lam, Yee Cheong; Lim, Yee Hwee
Highlights: Effects of flow rates and junction angle θ were investigated for 20° ≤ θ ≤ 160°. Theoretical model to predict gas bubble and liquid slug sizes was established. For θ = 20°, unit cell ↓ significantly with ↓ liquid or ↑ gas flow rate. For 45° ≤ θ ≤ 160°, unit cell is less sensitive to flow rate change and < θ = 20°. Abstract: Two-phase liquid-gas Taylor flow triggered by blocking-squeezing mechanism was studied with different junction angle θ microchannels, i.e. 20°, 45°, 90°, 135° and 160°, at various liquid (ethanol) and gas (He) flow rates. We experimentally investigated the effects of flow rates and θ on the gas bubble VB and liquid slug VS volumes. A theoretical model was formulated for the quantitative predictions of bubble and slug sizes for different θ and flow rates. Good agreements were obtained between theoretical predictions and experimental observations. The unit cell volume VU ( VB + VS ) decreased pronouncedly for the 20° channel with decreasing liquid or increasing gas flow rate, due to the slight increase in VB and large decrease in VS . In comparison, for the 45°, 90°, 135° and 160° channels with increasing liquid or decreasing gas flow rate, VU were less sensitive to fluid flow rate changes, due to the approximate cancellation between VB decrease and VS increase. For the 20° and 45° channels, it produced larger VU, due to larger VB and VS, when compared to the 90° channel. This is caused by the larger gas bubble throat width DN at the junction when θ < 90°. As for the 135° and 160° channels ( θ > 90°), DN is approximately equal to the gas channel width, with VB, VS and VU approximately the same as the 90° channel. With θ ≥ 90° (i.e. 90°, 135° and 160° channels), as evident from the smaller VU, higher gas bubble density can be obtained when compared to θ < 90° (i.e. 20° and 45° channels). Hitherto, this observation has not been realized, and the mechanics is first investigated here with the employment of extreme θ (i.e. 20° and 160°). A thorough understanding of the underlying mechanics affecting Taylor flow can facilitate its exploitation for controlled gas bubble and liquid slug generation. Our theoretical model facilitates the tuning of the channel designs and fluid flow rates to achieve the desired gas bubble and liquid slug sizes for specific applications.